The way things are : conversations with Huston Smith on the spiritual life - Smith, Huston (University of California Press, 2003)
Where can we find what is ultimately meaningful? How can we discover what is truly worth knowing? In one form or another Huston Smith has been posing these questions to himself--and the world--all his life. In the course of seeking answers, he has become one of the most interesting, enlightening, and celebrated voices on the subject of religion and spirituality throughout the world.
Keywords: Smith, Huston -- Interviews.; Smith, Huston; Religion historians -- United States -- Interviews.; Religion.; Spiritual life.; Religion and science.; Religion; Religion and Science; Historiens de la religion -- États-Unis -- Entretiens.; Vie spirituelle.; Religion et sciences.; religion (discipline); BIOGRAPHY & AUTOBIOGRAPHY -- Religious.; RELIGION -- Clergy.; RELIGION -- Comparative Religion.; Religion and science; Religion historians; Spiritual life; United States; Spiritualiteit.; Godsdienst.; Wetenschap.; Interview; interviews.; Interviews; Interviews.